The metal-rich universe - Israelian, Garik; Meynet, G. (Cambridge contemporary astrophysics., 2008)
Metal-rich stars accumulate their metals from previous generations of stars, & contain the history of their galaxy. By studying these stars we can gain valuable insights into how metals change the formation & evolution of stars, & explain the extraordinary massive star populations observed in our own galaxy.